Politik Hukum Mahkamah Konstitusi sebagai Lembaga Penyelesaian Sengketa Hasil Pilkada Tahun 2024 di Indonesia: Studi Kasus Putusan Nomor 69/Phpu.Bup-Xxiii/2025 Kabupaten Pulau Morotai - Faturahman Djaguna (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the legal politics dynamics of the Constitutional Court (Mahkamah Konstitusi/MK) as an institution for resolving regional election (Pilkada) disputes in Indonesia in 2024, using Decision Number 69/PHPU.BUPXXIII/2025 concerning the electoral dispute in Pulau Morotai Regency as a case study. The study employs normative legal research with a statutory and case-based approach, supported by three theoretical frameworks: Montesquieu's separationof-powers (trias politica) theory, Mahfud MD's legal politics theory and Jürgen Habermas's deliberative democracy theory. Primary legal materials, comprising the Constitutional Court's decision and relevant legislation, are analyzed descriptively and qualitatively. The findings show that the Constitutional Court's authority over regional election disputes has undergone significant institutional change, from the transfer of authority through Decision Number 97/PUU-XI/2013 to its permanent consolidation through Decision Number 85/PUU-XX/2022. In Decision Number 69/PHPU.BUP-XXIII/2025, the Court declared the petition inadmissible because the petitioner failed to meet the vote-margin threshold under Article 158 paragraph (2) letter a of Law Number 10 of 2016, so that the Court's legal politics is reflected in the strict application of this formal filter without any examination of the substance of the alleged violations. The decision carries juridical implications for electoral legal certainty in Pulau Morotai Regency while raising questions about the balance between procedural efficiency and substantive justice from the standpoint of deliberative democracy.